2005
DOI: 10.1002/dvdy.20408
|View full text |Cite
|
Sign up to set email alerts
|

Expression of all Wnt genes and their secreted antagonists during mouse blastocyst and postimplantation development

Abstract: In this extensive study, real-time reverse transcriptase-polymerase chain reaction was used to analyze the expression levels of all 19 Wnt genes and their 11 potential antagonists in mouse blastocysts, pregastrula, gastrula, and neurula stages. By complementing these results with in situ hybridization, we revealed new expression domains for Wnt2b and Sfrp1, respectively, in the future primitive streak at the posterior side and in the anterior visceral endoderm before the initiation of gastrulation. Moreover, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
158
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(164 citation statements)
references
References 100 publications
(156 reference statements)
5
158
0
Order By: Relevance
“…In the gastrula, candidate antagonists include secreted frizzled-related protein 1 (Sfrp1), Sfrp2, Sfrp3 (Frzb1), Sfrp5, Crescent, and Dkk1, all of which are expressed in the anterior mesendoderm (Leyns et al 1997;Glinka et al 1998;Pilcher and Krieg 2002;Finley et al 2003;Kemp et al 2005). Sfrps sequester Wnt ligands in the extracellular space, preventing them from binding to Frizzled receptors, and thus can inhibit both canonical and noncanonical signaling (Kawano and Kypta 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the gastrula, candidate antagonists include secreted frizzled-related protein 1 (Sfrp1), Sfrp2, Sfrp3 (Frzb1), Sfrp5, Crescent, and Dkk1, all of which are expressed in the anterior mesendoderm (Leyns et al 1997;Glinka et al 1998;Pilcher and Krieg 2002;Finley et al 2003;Kemp et al 2005). Sfrps sequester Wnt ligands in the extracellular space, preventing them from binding to Frizzled receptors, and thus can inhibit both canonical and noncanonical signaling (Kawano and Kypta 2003).…”
mentioning
confidence: 99%
“…In contrast, Dkk1 specifically inhibits the canonical Wnt pathway by binding to LRP6 (Mao et al 2001;Semenov et al 2001). To date, the genetic analysis of Wnt antagonists in the mouse has not revealed a function in foregut development; however, their overlapping expression patterns suggest extensive redundancy (Leimeister et al 1998;Finley et al 2003;Kemp et al 2005). Indeed, mutations in dkk1, sfrp1, sfrp2, or sfrp5, as well as various double and triple mutants, indicate that they have redundant roles in axial trunk formation, but foregut defects have not yet been described in these embryos (Mukhopadhyay et al 2001;Leaf et al 2006;Satoh et al 2006Satoh et al , 2008.…”
mentioning
confidence: 99%
“…AME expresses signaling ligands such as SHH (Shimamura and Rubenstein, 1997;Gunhaga et al, 2000) and BMP7 (Furuta et al, 1997), and modulators of signaling activity including CHRD, NOG, CER-BERUS, and DKK1 (Biben et al, 1998;Belo et al, 2000;Anderson et al, 2002;Kemp et al, 2005) which act synergistically to regulate the temporal-spatial activity of signaling pathways for forebrain induction and patterning (Dale et al, 1997(Dale et al, , 1999del Barco Barrantes et al, 2003). We have shown that deficiency of IIA in mice results in loss of expression of Shh in the prechordal plate and reduced Six3 and Pax2 expression in the forebrain, and phenocopies the malformation of the prosencephalon and mid-facial structures of the Shhnull mutant (Chiang et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Wnt7b was also shown to be another potential FZD ligand at this stage of development and to be expressed throughout the blastocyst [67]. However, Wnt7b expression was restricted to the extraembryonic region of the forming egg cylinder at implantation, 4.75 dpc [8] Among Wnt ligands expressed in the mouse blastocyst (e.g., Wnts 4, 5b, 7b, 10b, 1, 5a, 7a, 11, and 13), a number of them are newly detectable in the blastocysts (Wnt 1, 5a, 7a, 11, and 13).…”
Section: Wnt Signaling In Pre-implantation Embryo Developmentmentioning
confidence: 98%